Impacts of manure application on SWAT model outputs in the Xiangxi River watershed - Liu, Ruimin; Wang, Qingrui; Xu, Fei; Men, Cong; Guo, Lijia (Journal of hydrology (Amsterdam), 2017)
•New manure database in SWAT model were built based on the actual manure amount.•New manure database resulted in less phosphorus pollution than the original manure.•Better calibration and validation values were obtained by using the new manure database. SWAT (Soil and Water Assessment Tool) model has been widely used to simulate agricultural non-point source (ANPS) pollution; however, the impacts of livestock manure application on SWAT model outputs have not been well studied. The objective of this study was to investigate the environmental effects of livestock manure application based on the SWAT model in the Xiangxi River watershed, which is one of the largest tributaries of the Three Gorges Reservoir in China. Three newly-built manure databases (NB) were created and applied to different subbasins based on the actual livestock manure discharging amount. The calibration and validation values of SWAT model outputs obtained from the NB manure application and the original mixed (OM) manure were compared. The study results are as follows: (1) The livestock industry of Xingshan County developed quickly between 2005 and 2015. The downstream of the Xiangxi River (Huangliang, Shuiyuesi and Xiakou) had the largest livestock amount, and largely accounted for manure, total nitrogen (TN) and total phosphorus (TP) production (>50%). (2) The NB manure application resulted in less phosphorus pollution (1686.35 kg for ORGP and 31.70 kg for MINP) than the OM manure application. Compared with the upstream, the downstream was influenced more by the manure application. (3) The SWAT results obtained from the NB manure had a better calibration and validation values than those from the OM manure. For ORGP, R2 and NSE values were 0.77 and 0.65 for the NB manure calibration; and the same values for the OM manure were 0.72 and 0.61, respectively. For MINP, R2 values were 0.65 and 0.62 for the NB manure and the OM manure, and the NSE values were 0.60 and 0.58, respectively. The results indicated that the built-in fertilizer database in SWAT has its limitation because it is set up for the simulation in the USA. Thus, when livestock manure is considered in a SWAT simulation, a newly built fertilizer database needs to be set up to represent the localized condition more accurately. The conclusions of this study would be instructive for livestock pollution simulations, and favorable for non-point source pollution prevention at the watershed scale.